2015
DOI: 10.3389/fgene.2014.00453
|View full text |Cite
|
Sign up to set email alerts
|

Whole-body transcriptome of selectively bred, resistant-, control-, and susceptible-line rainbow trout following experimental challenge with Flavobacterium psychrophilum

Abstract: Genetic improvement for enhanced disease resistance in fish is an increasingly utilized approach to mitigate endemic infectious disease in aquaculture. In domesticated salmonid populations, large phenotypic variation in disease resistance has been identified but the genetic basis for altered responsiveness remains unclear. We previously reported three generations of selection and phenotypic validation of a bacterial cold water disease (BCWD) resistant line of rainbow trout, designated ARS-Fp-R. This line has h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
82
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 64 publications
(87 reference statements)
4
82
0
Order By: Relevance
“…GPB1 gene transcript also shows correlated expression with lncRNA in human26. Previous reports suggested that gbp1 is one of the differentially regulated immune response genes against microbial pathogens in salmon and trout927.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…GPB1 gene transcript also shows correlated expression with lncRNA in human26. Previous reports suggested that gbp1 is one of the differentially regulated immune response genes against microbial pathogens in salmon and trout927.…”
Section: Resultsmentioning
confidence: 77%
“…Previously, we analyzed mRNA expression in three genetic lines of fish sampled at 1 and 5 days post- Fp challenge9. In our prior analyses, slightly more than half (51.77%) of the RNA-Seq reads aligned to the 46,585 predicted coding mRNAs and thus considerable sequence information remained unaligned and thus enigmatic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These resources will provide powerful tools for the research community and will aid in the determination of the genetic factors involved in the regulation of complex traits. For example, high-throughput RNA sequencing can give a holistic view of the host response to infectious diseases, and help identify the important genes and pathways defining genetic resistance, as demonstrated in this issue for rainbow trout (Ali et al, 2014;Marancik et al, 2014) and panaeid shrimp (Santos et al, 2014). Sequencing technology has also facilitated the development of abundant genetic markers that have multi-faceted applications for selective breeding of aquatic species, including parentage assignment in mixedfamily environments, providing greater control over family representation and inbreeding (Vandeputte and Haffray, 2014).…”
mentioning
confidence: 99%